1991
DOI: 10.1093/infdis/163.2.346
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Functional Activities between IgG1 and IgM Class-Switched Human Monoclonal Antibodies Reactive with Group B Streptococci or Escherichia coli K1

Abstract: The influence of valence and heavy chain on antibody activity was investigated using transfectoma-derived, class-switched IgG1 and IgM human monoclonal antibodies (MAbs) reactive with the bacterial pathogens Escherichia coli K1 and group B Streptococcus species. IgG-IgM pairs were compared in vitro for antigen binding and opsonic activities and in vivo for protective efficacy in neonatal rats. For the anti-E. coli pair, the IgM MAb was 1000-fold more potent in all assay formats. Importantly, the 50% protection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 33 publications
2
31
1
Order By: Relevance
“…On the other hand, the chIgM antibodies had at least a 50-times-higher OP activity on a molar basis than chIgG3 in our test system. A similar high OP activity of human chIgM over human IgG1 has been observed for anticarbohydrate antibodies against the Gram-positive group B streptococci [33,34].…”
Section: Discussionsupporting
confidence: 68%
“…On the other hand, the chIgM antibodies had at least a 50-times-higher OP activity on a molar basis than chIgG3 in our test system. A similar high OP activity of human chIgM over human IgG1 has been observed for anticarbohydrate antibodies against the Gram-positive group B streptococci [33,34].…”
Section: Discussionsupporting
confidence: 68%
“…In contrast, low levels of anti-PPS IgM antibodies can account for the functional difference observed between young and old adults immunized with PPV23, since IgM is more efficient at fixing complement than IgG. Indeed, studies with human monoclonal antibodies have shown that IgM antibodies can be 10-to 100-fold more effective than IgG antibodies at opsonizing bacteria or protecting animals from infections (30,39). Some IgM antibodies that are protective against bacterial infections bind many unrelated antigens, such as singlestranded DNA, thyroglobulin, and ␤-galactosidase (27).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, expressing a mAb as a multivalent isotype, such as SIgA or IgM, can dramatically enhance the potency of an antibody by increasing the avidity (96) or agglutination activity (14). For example, an anti- Escherichia coli IgM was 1,000-fold more effective in protecting neonatal rats than its class-switched IgG (both in vitro and in vivo) (41). From a commercial standpoint, a 1,000-fold increase in avidity could translate into a 1,000-fold decrease in dose and subsequent cost.…”
Section: Recent Advances In Mab Technologymentioning
confidence: 99%